The Effect of Differentiated Learning Based on the Independent Curriculum on Instructional Media Usage at SMA Negeri 1 Pare - Dinil Abrar Sulthani; Tahir Tahir; Suprapto Suprapto; Kunaenih Kunaenih (The Future of Education Journal, 2026)
Differentiated learning, which is adapted to students’ levels of comprehension and individual learning needs, presents a considerable challenge for educators in selecting and tailoring instructional media at SMA Negeri 1 Pare, Kediri. By implementing this pedagogical approach, teachers can optimize media selection to enhance the effectiveness of Islamic Religious Education (PAI) classroom instruction. This quantitative study, employing a survey methodology, aimed to investigate and analyze the influence of differentiated learning on students’ utilization of PAI instructional media. Data were collected through observation and structured questionnaires administered to 21 respondents. Product-moment correlation analysis was utilized to examine the relationship between the independent and dependent variables. The findings revealed that differentiated learning exerts a substantial and significant influence, accounting for 70% of the variance in instructional media utilization. Specifically, the study established that: (1) teachers designed instruction with objectives and assessments explicitly aligned with student learning needs; (2) teachers employed diverse media to accommodate varying proficiency levels; (3) teachers provided systematic instructional scaffolding for both offline and online media use; and (4) differentiated learning successfully enhanced student motivation and autonomy in media engagement and task completion. The study concludes that differentiated learning, as operationalized within the framework of the Independent Curriculum, is demonstrably relevant and effective for optimizing PAI instruction at the senior high school level.